Evaluation of Resonance Strengths and Reaction Rates of 22Ne (p, gamma) 23Na Nuclear Reaction at Thermonuclear Energies - A.Selman, Ahmed (Iraqi Journal of Physics, 2023)
At thermal energies near stellar conditions, nuclear reactions are sensitive to resonance strengths of the nuclear reaction cross-section. In this paper, the resonance strengths of  nuclear reaction were evaluated numerically by means of nuclear reaction rate calculations using a written Matlab code, at the energies of interest in stellar nuclear reactions. The results were compared with standard reaction before and after application of statistical analyses, to select the best parameters that made theoretical results as close as possible to the standard values. Fitting was made for different temperature ranges up to 10 GK, 0.6 GK and 0.25 GK. The evaluated results showed that as the temperature range becomes narrower, more error is added to the evaluated strengths. A proper strength value based on the most recent measured one suggested the difference of at least one order of magnitude can be solved using a numerical evaluation for energies less than 650 keV.